Sistem Pendukung Keputusan Untuk Pemeringkatan Koperasi Pada Dinas Perindustrian, Perdagangan Dan Koperasi Dengan Metode AHP (Analytic Hierarchy Process) (Studi kasus pada Dinas Perindustrian Perdagangan dan koperasi Kota Metro,lampung) - kenali, fitria; Mustika, Diah (Jurnal Informatika, 2011)
Decision support system is a system that can help the Department of Industry, Trade and Cooperatives in making decisions with the ability to determine the quality of cooperatives using AHP (Analytic Hierarchy Process), in which each criterion in this case the alternative assessment factors compared with one others so as to provide the output intensity value priorities that result in a system that provides an assessment of each cooperative in metro cities. This decision support system to the selection of each cooperative. With a selection value then it is useful to facilitate decision making on issues related to the tender auction, so we get the most viable cooperatives to serve as a quality cooperative. Keywords: Decision Support System (DSS), Ranking, AHP (Analytic Hierarchy Process).